2021
DOI: 10.1177/1357633x211066235
|View full text |Cite
|
Sign up to set email alerts
|

Use and impact of virtual primary care on quality and safety: The public's perspectives during the COVID-19 pandemic

Abstract: Introduction With the onset of Coronavirus disease (COVID-19), primary care has swiftly transitioned from face-to-face to virtual care, yet it remains largely unknown how this has impacted the quality and safety of care. We aim to evaluate patient use of virtual primary care models during COVID-19, including change in uptake, perceived impact on the quality and safety of care and willingness of future use. Methodology An online cross-sectional survey was administered to the public across the United Kingdom, Sw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
2
10
0
1
Order By: Relevance
“…There has been substantial research into the safety and validity of virtual care, 7 and most patients have favorable views of using virtual care (even more so during the pandemic). 8 However, there has been little discussion on the potential environmental and fiscal benefits that society may derive from virtual care. The objective of this study was to estimate the environmental and patientlevel financial benefits associated with the widespread adoption of virtual care during the COVID-19 pandemic.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been substantial research into the safety and validity of virtual care, 7 and most patients have favorable views of using virtual care (even more so during the pandemic). 8 However, there has been little discussion on the potential environmental and fiscal benefits that society may derive from virtual care. The objective of this study was to estimate the environmental and patientlevel financial benefits associated with the widespread adoption of virtual care during the COVID-19 pandemic.…”
Section: Key Pointsmentioning
confidence: 99%
“…There has been substantial research into the safety and validity of virtual care, and most patients have favorable views of using virtual care (even more so during the pandemic) . However, there has been little discussion on the potential environmental and fiscal benefits that society may derive from virtual care.…”
Section: Introductionmentioning
confidence: 99%
“…Our cohort reported that problems with using remote and digital services served as a barrier to medicines access, so this mismatch in provider and patient expectations needs to be addressed to avoid access problems. A recent review of policy around virtual and remote healthcare suggests that work is needed to address "shortcomings exposed during COVID-19" (Neves et al 2021c). We suggest that more needs to be done to enhance people's capabilities and opportunities, if necessary, beyond the digital sphere through home visits, health visitors or mail, or targeting face-to-face consultations where a benefit is likely to be greatest.…”
Section: What This Study Addsmentioning
confidence: 97%
“…Dit kan leiden tot ongelijkheid in de zorg. 26,27 Ook huisartsen verschillen in hun digitale vaardigheden en interesses. Bij de introductie van digitale ondersteuning moet er voldoende aandacht zijn voor training en scholing.…”
Section: De Kernunclassified